Using drama in the Palestinian EFL classroom: teachers’ attitudes, advantages, problems, and teaching techniques - Mohammed Farrah; Balsam Halahla; Shahd Sider (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2021)
The use of drama activities is a method that allows learners to improve their communication skills, think critically, learn new vocabulary, and increase their motivation for learning. This study investigates the attitudes of English language teachers, as well as the advantages, problems faced in, and teaching techniques of the English language learning process in Palestinian schools using drama activities. Using both qualitative and quantitative research methods, the researchers investigated the extent to which drama activities are used while teaching English as a second language in Palestinian schools using a questionnaire and interviews. In the questionnaire, the participating English language teachers were 39 females and 12 males. Two teachers were interviewed. The findings confirm the need to implement changes and improvements regarding the use of drama activities in the language classroom. Moreover, the findings suggest following specific drama usage recommendations to ensure satisfactory results for both teachers and students to improve the four language skills. The implication of this study calls for providing clear and sufficient materials for drama classes, as well as offering teachers training programs to enhance their abilities to use drama activities in an effective way.